The effects of diffuser profile on the performance of the liquid-gas ejector - Salim, Amat Agus; Sugati, Daru (Universitas Muhammadiyah Surakarta, 2023)
Kinetic energy originating from liquid jets at high speed can be used as an energy source for liquid-gas ejector devices. An ejector is a tool often used to support one of the processes in the industry, such as vacuum process, desalination, distillation, and refrigeration. The ejector consists of several main components: the nozzle, suction chamber, mixing chamber or throat, and diffuser. These components influence each other, so that system performance is sensitive to the performance of these components. The diffuser functions as a dynamic head converter into a static head. Its performance is affected by its dimensions, so it needs to be investigated. This study aims to determine the effect profile of a diffuser with a divergence angle of 2β 7° and a diffuser with a tiered divergence angle of 2β. This study uses an experimental method with a motive flow pressure for the primary fluid of 201.32 kPa. This study found that changes in length and the angle of divergence of the diffuser affect the value of the pressure recovery coefficient and efficiency.